GAMBARAN PENYESUAIAN DIRI GURU DI WILAYAH PEDALAMAN - Herdiyan Maulana; Nancy Riana (MANASA, 2012)
This research was aimed to get more comprehensive description about the teacher adjustment in rural area. The research approach used was case research. Data was gained by using observation, interview, and documentation techniques. Characteristics of the person is the teacher who is a pioneer in the teaching of SDS in Sungai Palembang, have a strong determination to become teacher in thecountryside, attended a school in Sungai Palembang and still works as a teacher in Sungai Palembang. The results of this study showed the subjects to make adjustments in dealing with the problems that exist for a teacher in Sungai Palembang. The problems of environmental conditions and school a minimum of problems and in the form of evicitions. Threats and fire at the beginning of a teacher in Sungai Palembang. The ability to control the emotions with patience and a sense of help the high teachers colleagues and stundets.